Daily summer monsoon rainfall over northeast India due to synoptic scale systems - MOHAPATRA, M.; BISWAS, H. R.; SAWAISARJE, G. K. (MAUSAM, 2008)
The summer monsoon rainfall over northeast India mostly depends on the synoptic systems over the region and neighbourhood and the convection due to the interaction of orography with the synoptic and sub-synoptic scale systems. Hence, an attempt is made to analyse the mean daily rainfall distribution over northeast India due to different synoptic systems like Low Pressure Systems (LPS) and cyclonic circulations (cycir) extending upto lower/middle tropospheric levels over different regions. The mean daily rainfall due to monsoon trough over various locations in northeast India is also analysed. For the above purpose, the rainfall data over 50 uniformly distributed stations in northeast India during summer monsoon season (June-September) for a period of 10 years (1991-2000) are considered. The principal objective of the study is to find out the contribution of the different synoptic systems to the spatial variability of monsoon rainfall over northeast India. The developed synoptic analog maps may be useful to the forecasters for 24 hours rainfall forecast with the knowledge of location, intensity and movement of the synoptic systems. Based on larger data set, the results confirm the earlier findings (Srinivasan et al., 1972) with respect to rainfall due to monsoon trough and LPS. The Low Level Cycir (LLC) also plays significant role on the rainfall variability over northeast India, as the number of LLC days is significantly higher over the region, contrary to the days of occurrence of LPS. The study finds out the regions of excess/deficient rainfall and active/weak monsoon conditions due to different synoptic systems.